Efektivitas Games PowerPoint dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam - Muh. Syahrul Hamka; Usman Usman; Abdul Halik; Hamdanah Hamdanah; Muzdalifah Muhammadun (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
Using a learning media adapted to the characteristics of students who like to play, designed through the application of PowerPoint presentations, is a solution for students' PAI learning outcomes. This research used a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 18 students: 9 in the experimental and 9 in the control classes. The research focused on student learning outcomes before and after using learning media based on PowerPoint games in third grade of SD Negeri 294 Lempa. The results showed that students' learning outcomes experienced an increase after using learning media based on PowerPoint games, as shown in the test results. The indicators can be seen from the pretest-posttest results. In the experimental class, the average pre-test score was 62.68, which increased to 81.1 after the post-test. In the control class, the pre-test score was 48.22 to an average of 50.66 after the post-test. The result of calculating the N-Gain Score for the experimental class was 59.40, which was categorized as quite effective, while the control class's N-Gain Score was 38.16, classified as ineffective.